2000
DOI: 10.1128/jb.182.15.4319-4327.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Evolution, and Essentiality of the Mevalonate Pathway for Isopentenyl Diphosphate Biosynthesis in Gram-Positive Cocci

Abstract: The mevalonate pathway and the glyceraldehyde 3-phosphate (GAP)-pyruvate pathway are alternative routes for the biosynthesis of the central isoprenoid precursor, isopentenyl diphosphate. Genomic analysis revealed that the staphylococci, streptococci, and enterococci possess genes predicted to encode all of the enzymes of the mevalonate pathway and not the GAP-pyruvate pathway, unlike Bacillus subtilis and most gram-negative bacteria studied, which possess only components of the latter pathway. Phylogenetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
205
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(214 citation statements)
references
References 51 publications
8
205
0
1
Order By: Relevance
“…Plasmid construction processes are listed in Supplementary Materials: Table S2. The genes encoding trans-nerolidol synthase (AcNES1; GenBank-KX064240) from Actinidia chinensis (Green et al, 2012), and 3-hydroxy-3-methylglutaryl-Coenzyme A (HMG-CoA) synthase (EfmvaS; GenBank-KX064238) and bi-functional acetoacetyl-CoA thiolase /HMG-CoA reductase (EfmvaE; GenBank-KX064239) from E. faecalis (Wilding et al, 2000) were synthesized by GenScript (Piscataway, NJ, USA) with codon optimization according to the codon bias of S. cerevisiae (Supplementary Materials: Table S3). .…”
Section: Plasmid and Strain Constructionmentioning
confidence: 99%
“…Plasmid construction processes are listed in Supplementary Materials: Table S2. The genes encoding trans-nerolidol synthase (AcNES1; GenBank-KX064240) from Actinidia chinensis (Green et al, 2012), and 3-hydroxy-3-methylglutaryl-Coenzyme A (HMG-CoA) synthase (EfmvaS; GenBank-KX064238) and bi-functional acetoacetyl-CoA thiolase /HMG-CoA reductase (EfmvaE; GenBank-KX064239) from E. faecalis (Wilding et al, 2000) were synthesized by GenScript (Piscataway, NJ, USA) with codon optimization according to the codon bias of S. cerevisiae (Supplementary Materials: Table S3). .…”
Section: Plasmid and Strain Constructionmentioning
confidence: 99%
“…In genetic studies that we performed on S. aureus, SA2343 was shown to be upregulated 100-500 fold when any of the genes in the mevalonate pathway, responsible for biosynthesis of the isoprenoid precursor isopentenyl pyrophosphate (IPP), is downregulated (Balibar et al, 2009). Given that IPP is the building block for the cell wall carrier lipid undecaprenyl pyrophosphate (UPP), which is essential in peptidoglycan biosynthesis (Wilding et al, 2000), this massive overexpression is presumed to be a response to cell wall damage. This upregulation of SA2343 was more than 20-fold greater than the upregulation of any other gene in the cell wall stimulon.…”
Section: Introductionmentioning
confidence: 99%
“…The MVA pathway is essential for the survival of Streptococcus pneumonia in the lung and serum. 13 It was reported that the product of PMK, diphosphomevalonate (DPM), feed-4 back inhibits MK in S. pneumonia. Therefore, regulation of the MVA pathway would provide novel therapies to intervene in the pathway to inhibit the devastating effect of the organism.…”
Section: Introductionmentioning
confidence: 99%